VITAL AND HEALTH STATISTICAL DATA COLLECTION AND ITS DIFFICULTIES IN IRAN - M Olfat (Tehran University of Medical Sciences, 1971)
The important items of health and treatment statistics are birth incidence, cause of death, contagious and chronic diseases, health facilities, man power, hospital services, health and treatment services in the area of environmental heath, health and family planning, public health education, laboratories affairs, control of tuberculosis, health services, etc. These statistical data are collected from hospitals, maternities, sanatoriums, clinics, medical centers, health centers, public health centers, whether governmental, half governmental, private or charity. However, 40 % of the morbidity data, 20 % of the cause of death, 80 % of facilities data, 54 % of hospital statistics and 80 % of activities data, and even those with deficiencies, are reported. The causes can be sought in the lack of cooperation by the half governmental organizations and charities, more particularly the private section and private physicians, lack of facilities for diagnosis of diseases, lack of possibilities for statistical sampling, insufficient number of well or sufficient trained statisticians, and finally, non-unified methods and data collection forms. In order to enhance the level of required health statistics, an executive committee for cooperation in health statistics, consistent of representatives of various organizations that have something to do with the issue of health, must be selected. This will result in cooperation and harmonious actions necessary for health programming. Guarantees of actions must be provided in order to carry out the present regulations. Statistics units must be instituted in all the treatment institutes. To produce motives of different groups for enhancing the statistical aspects, education in health statistics must be given in the levels of: 1) specialized and professional groups of statisticians; 2) medical and related groups; and 3) the general population. These can be achieved by radio and television programs, newspapers and editorials, seminars, conferences, and holding classes.